Concurrent lymphovascular and perineural invasion after preoperative therapy for gastric adenocarcinoma is associated with decreased survival. Issue 4 (5th January 2021) - Blumenthaler, Alisa N.; Newhook, Timothy E.; Ikoma, Naruhiko; Estrella, Jeannelyn S.; Blum Murphy, Mariela; Das, Prajnan; Minsky, Bruce D.; Ajani, Jaffer A.; Mansfield, Paul F.; Badgwell, Brian D.
Abstract: Background and Objectives: We sought to evaluate the impact of lymphovascular invasion (LVI) and perineural invasion (PNI) on survival outcomes in gastric cancer patients treated with preoperative therapy. Methods: Patients with gastric cancer treated with preoperative therapy and potentially curative resection were stratified according to the presence of LVI, PNI, or both. Kaplan–Meier and Cox regression analyses were used to evaluate the impact on overall survival (OS) and disease‐free survival (DFS). Results: The study included 281 patients, of whom 93 (33%) had LVI, 69 (25%) had PNI, 51 (18%) had both LVI and PNI, and 170 (61%) had neither. LVI and PNI were each associated with higher ypT and ypN categories and more positive lymph nodes (all p  < .001), associations that were emphasized with both factors present. On multivariable analyses, ypN ( p  < .001) and concurrent LVI/PNI (hazard ratio [HR]: 2.62; 95% confidence interval [CI]: 1.55–4.45; p  = .001) were predictive of OS and DFS (ypN: p  < .001; both LVI/PNI: HR: 2.27; 95% CI: 1.34–3.82; p  = .002). Conclusions: Gastric cancer patients with concurrent LVI and PNI after preoperative therapy have more advanced disease and worse survival outcomes than patients with neither or only one of these factors.